Patton - Malden, Karl.; McCarthy, Frank, 1912-1986.; Schaffner, Franklin J.; Scott, George C., 1927-1999.; Twentieth Century Fox Home Entertainment, Inc.; Twentieth Century-Fox Film Corporation (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2001)
Story of General Patton in World War II whose military brilliance was balanced by his inability to deal with the social and political aspects of war, causing him difficulties in his dealings with the War Department
Winner of 8 academy awards including best picture 1970
Keywords: Patton, George S. -- 1885-1945 -- Drama; Generals -- United States -- Biography -- Drama; World War, 1939-1945 -- Drama